2022
DOI: 10.3390/buildings12111901
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Optimal Design and Seismic Capacity of Double-Span RC Frame Structures with Exterior Verandahs

Abstract: Frame structures with exterior verandahs, which are mostly built in densely populated areas such as teaching buildings and dormitories in southern China, are a special form of frame structure that must continue to be developed. However, compared with other frame structures in many post-earthquake fields, this type of building designed following the Chinese code has demonstrated poor seismic performance, leading to a significant number of casualties and property losses. Therefore, to complement the design requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The previous analysis revealed that the TMSR-LF1 plant structure cannot meet the seismic design goal of "no collapse in large earthquakes" during seismic analysis by the elastoplastic time history analysis. Therefore, adequate reinforcement [27,35,36] is imperative. Since the damage of the structure mainly occurs in the aboveground part, the following three measures have been recommended to enhance and reinforce the structure components above +0 m elevation: (1) the column crosssectional size of the structure will be upgraded from 600 mm × 600 mm to 800 mm × 800 mm; (2) the infill wall and shear wall components on both sides of the exterior wall and aisle of the structure will be modified to shear walls with an 800 mm thickness; (3) the infill wall elements in Advances in Civil Engineering other areas of the structure will be replaced with shear walls with a thickness of 400 mm.…”
Section: Structural Reinforcement Analysismentioning
confidence: 99%
“…The previous analysis revealed that the TMSR-LF1 plant structure cannot meet the seismic design goal of "no collapse in large earthquakes" during seismic analysis by the elastoplastic time history analysis. Therefore, adequate reinforcement [27,35,36] is imperative. Since the damage of the structure mainly occurs in the aboveground part, the following three measures have been recommended to enhance and reinforce the structure components above +0 m elevation: (1) the column crosssectional size of the structure will be upgraded from 600 mm × 600 mm to 800 mm × 800 mm; (2) the infill wall and shear wall components on both sides of the exterior wall and aisle of the structure will be modified to shear walls with an 800 mm thickness; (3) the infill wall elements in Advances in Civil Engineering other areas of the structure will be replaced with shear walls with a thickness of 400 mm.…”
Section: Structural Reinforcement Analysismentioning
confidence: 99%
“…Improved mathematical models of physical phenomena, coupled with more and more complex numerical models of civil engineering structures, resulted in accurate assessments of their behaviour under various loading conditions. Numerical simulations are now at the heart of every major research project, from reliability analyses [1,2], to assessing the behaviour of different structures in difficult site conditions [3][4][5], to optimizing the design process and increase the safety of newly built or strengthened buildings [6][7][8][9][10], to creating intervention strategies and relief plans in case of occurring natural disasters [11]. Time-history analysis (THA) is based on direct step-by-step integration of the equation of motion in time domain considering as input either the recorded accelerograms of real earthquakes or synthetically / artificially generated ones to fit design elastic response-spectra of different design codes.…”
Section: Introductionmentioning
confidence: 99%